On-Call Duties: The Perceived Impact on Veterinarians' Job Satisfaction, Well-Being and Personal Relationships - Kogan, Lori; Schoenfeld-Tacher, Regina; Carney, Patrick; Hellyer, Peter; Rishniw, Mark (Frontiers in Veterinary Science, 2021)
On-call work is defined as times during which employees have to be available to be called into work if needed. During these shifts, employees may remain off-site, but must be ready to return to their duties quickly if summoned by an employer. This type of shift work has been shown to have negative effects on the emotional wellbeing of medical providers in general. This study assessed the impact of on call duties on veterinarians’ job satisfaction, well-being and personal relationships. A cross-sectional survey was conducted on a sample of Veterinary Information Network (VIN) members in private practice within the United States. A link to an anonymous online survey was distributed via an email invitation to all Veterinary Information Network (VIN) members with access from August 15, 2017- October 21, 2017. A total of 1945 responses were recorded. The majority of those who reported having on call duties were female associates. A composite scale was created to assess the impact of on call shifts on job satisfaction, with results indicating a greater negative impact for female associates compared to male associates or owners of either gender. Similar results were found when assessing well-being. There were no differences in the impact of on call shifts on personal relationships based on gender or ownership status. This study suggests that on call shifts have a negative impact on veterinarian job satisfaction, well-being and personal relationships. The negative impact on job satisfaction and well-being is greatest for female associates. Veterinary medicine has been identified as a stressful occupation that can lead to psychological distress. It is therefore important to critically assess current practices that appear to increase stress and reduce emotional wellbeing. For this reason, it is suggested that veterinary hospitals explore alternative options to traditional on call shifts.